Meta-Analysis Of Wakaf Based Sharia Microfinance Institutions: Meta-Analysis Lembaga Keuangan Mikro Syariah Berbasis Wakaf - Khaer, Rijalul; Firmansyah, Atep; Saepul Rohman, Pupun (Perisai : Islamic Banking and Finance Journal, 2023)
The purpose of writing this article is to examine the development of waqf-based Islamic Microfinance Institutions research in the world. The method used in this study is meta-analysis using data sources from articles published in international journals. The results show that there has been an increase in the development of IMFI waqf-based research from year to year. Many studies related to waqf based IMFI have been carried out with several countries in the world as case studies. A country that has become a lot of case studies in research related to this theme is Malaysia. In addition, based on the methodological approach used, the dominance of research was carried out using a qualitative approach. The paper that is widely cited is "Banking for the poor: The role of Islamic banking in microfinance initiatives". In addition, the author who often conducts research related to IMFI-based waqf is Mohamed Asmy bin Mohd Thas Thaker. The results of the analysis show that the management of cash waqf carried out by Islamic microfinance institutions is a solution to the current economic problems of the people. The potential of this waqf can later be used as a means of empowering the economy of the middle and lower classes with the role played by Islamic microfinance institutions. The implications of this research can be a reference for various stakeholders, especially the government, in the distribution of potential waqf managed by Islamic microfinance institutions.